2011
DOI: 10.1111/j.1365-2664.2011.02044.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing nontarget recaptures of an endangered predator using conditioned aversion and reward removal

Abstract: Summary 1.Live-trapping is a fundamental tool in the study of wildlife species and populations. Capture of nontarget species is an inherent side-effect of trapping animals that is inefficient and potentially detrimental to individuals and populations. Reducing recapture of nontarget species will increase the efficiency of long-term studies and projects, and minimize unwanted impacts. 2. During the initial stages of a 3-year feral cat Felis catus control programme on San Clemente Island, California, USA, we exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Habituation to predator scented foraging trays is therefore possible, but has not been described previously. Recapture of 'trap-happy' individuals often occurs in trapping studies (Phillips & Winchell 2011), and a similar phenomenon may have occurred in the current study, with rock rats repeatedly visiting trays due to an association of the apparatus with food.…”
Section: Discussionsupporting
confidence: 80%
“…Habituation to predator scented foraging trays is therefore possible, but has not been described previously. Recapture of 'trap-happy' individuals often occurs in trapping studies (Phillips & Winchell 2011), and a similar phenomenon may have occurred in the current study, with rock rats repeatedly visiting trays due to an association of the apparatus with food.…”
Section: Discussionsupporting
confidence: 80%
“…For example, Short et al (2012) showed that a careful neck snare design improved selectivity without sacrificing efficiency to capture red foxes in the UK. In addition, modifying the cage-trap baiting strategy significantly reduced the recapture rate of an endangered non-target fox species in an island in California (USA), maintaining the capture rate of targeted feral cats (Phillips & Winchell 2011). In our study, the combination of live bait and fox urine improved cage-trap efficiency to capture red foxes, which would likely satisfy hunters' demand.…”
Section: Variablementioning
confidence: 78%
“…Animal conservation incorporates diverse policies and wildlife management methods, and some, including reintroductions [4] , trapping [5] , invasive species mitigation [6] , and deterrents [7] rely on manipulating animals’ behavioural responses. These interventions could be improved with insights from comparative cognition.…”
Section: Why Cognition?mentioning
confidence: 99%
“…However, with careful planning, operant conditioning can be a highly effective conservation tool. For example, wildlife managers successfully reduced trappings of native species while managing feral cat populations through aversive conditioning by fostering associations between a negative cue (nausea-inducing chemicals in trapping baits) and the experience of feeding in the trap [5] .…”
Section: Learningmentioning
confidence: 99%